Evaluating the Impact of Digital Health Policies on Nutritional Care Efficiency and Quality at the Primary Care Level - Dita Rosyalita; Icha Elyanida (Mandalika Journal of Medical and Health Studies, 2026)
This study evaluates the impact of digital health policies on the efficiency and quality of nutritional care at the primary care level, with a particular focus on the integration of Artificial Intelligence (AI). As primary care centers face challenges in delivering efficient and quality nutrition services, digital health technologies, especially AI-based tools, have emerged as potential solutions. This research reviews existing literature to explore how digital health policies, particularly those incorporating AI, have transformed nutritional care by improving service delivery, personalizing care, and enhancing access to underserved populations. Findings indicate that AI-driven tools help healthcare providers streamline administrative tasks, personalize nutritional assessments, and improve patient outcomes. However, challenges such as limited infrastructure, ethical concerns, and the need for healthcare worker training remain significant barriers to full implementation. The study suggests that while digital health policies hold promise, their effectiveness depends on addressing these challenges and ensuring proper support at the primary care level.